Factótum virtual tutor for the study of the functions - Vílchez Quesada, Enrique (2013)
We present the current status of a research project with the main purpose to provide both students and teachers of Mathematics, to level nationally, a system capable of supporting multimedia theme study in secondary roles. The project comprises all steps required for the development of virtual tutor and corresponding validation by potential users. As one of the steps mentioned above, we applied a diagnostic questionnaire to three high school groups from both public and private institutions located in different social sectors of Costa Rica (rural, urban and urban fringe) and ten secondary school teachers to determine the cognitive needs of students in this subject and system requirements subsequently developed and is presented as part of this article.